Hybrid Plasmonic–Photonic Panda-Ring Antenna Embedded with a Gold Grating for Dual-Mode Transmission - Sirigiet Phunklang; Atawit Jantaupalee; Patawee Mesawad; Preecha Yupapin; Piyaporn Krachodnok (Technologies, 2026)
This paper presents a systematic numerical investigation of a hybrid plasmonic–photonic Panda-ring antenna with an embedded gold grating, designed to enable efficient dual-mode radiation for optical and terahertz communication systems. The proposed structure integrates high-Q whispering-gallery mode (WGM) confinement in a multi-ring dielectric resonator with plasmonic out-coupling at the metal–dielectric interface, allowing controlled conversion of resonantly stored photonic energy into free-space radiation. The electromagnetic behavior is analyzed through a hierarchical structural evolution, progressing from a linear silicon waveguide to single-ring, add–drop, and Panda-ring resonator configurations. Gold is modeled using a dispersive Drude formulation with complex permittivity to accurately capture frequency-dependent plasmonic response at 1.55 µm. Power redistribution within the resonator system is described using coupled-mode theory, with coupling and loss parameters evaluated consistently from full-wave numerical simulations. Full-wave simulations using OptiFDTD and CST Studio Suite demonstrate that purely photonic resonators exhibit strong WGM confinement but negligible radiation, while plasmonic gratings alone suffer from low efficiency due to the absence of coherent photonic excitation. In contrast, the proposed hybrid Panda-ring antenna achieves stable and directive far-field radiation under WGM excitation, with a realized gain of approximately 8.05 dBi at 193.5 THz. The performance enhancement originates from synergistic hybrid SPP–WGM coupling, establishing a WGM-driven radiation mechanism suitable for Li-Fi and terahertz wireless applications.
Keywords: Plasmonic and Surface Plasmon Research; Photonic and Optical Devices; Metamaterials and Metasurfaces Applications